De-radicalization Policy in Nigeria: A Focus on Operation Safe Corridor - Doho, Ahmed Wali (Kashere Journal of Politics and International Relations, 2023)
The Operation Safe Corridor was created in 2016 after the Government of Nigeria realized that it would not defeat the Boko Haram insurgents by military means alone. This was deliberately targeted at low-level jihadist recruits by the two main factions – Jama’tu Ahlis Sunna Lidda’awati wal-Jihad and Islamic State in West Africa Province (ISWAP). The rehabilitation program involves vocational training, access to De- radicalization and civic programs. But many Nigerians expressed skepticism while some feel that there is a need for sufficient community consultation before the development and implementation of the program. The research being qualitative in nature relied on secondary sources of data, this is due to difficulties in tracing the ex-insurgents for interview and also the volatile nature of the villages they came from. At the end of the work, it was revealed that the program is faced with the problem of integrating the graduates in their communities, and there is also the problem of perception of the program by affected communities in the region. It was therefore recommended that the government should embark on sensitization with a view to educate the people in the area.